2011
DOI: 10.2174/1874325001105010001
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Predifferentiation of Human Bone Marrow-Derived Stem Cells by Short-Term Mechanical Stimulation

Abstract: It is commonly accepted that bone marrow-derived stem cells (BMSCs) have to be expanded in vitro, but a prolonged time in culture decreases their multilineage potential. Mechanical and biological stimuli have been used to improve their osteogenic potential. While long-term stimulation has been shown to improve osteogenic differentiation, it remains to be seen whether short-term stimulation is also sufficient.We investigated the influence of 24 hours' cyclic loading (0.05Hz, 4kPa) on gene expression of human BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…In a study by Matziolis et al, BM-derived hMSCs were cultured on human cancellous bone-fibrin composites (15 mm diameter and 4 mm thickness) in a compression bioreactor, and the effect of short term mechanical stimulation (24-hour cyclic loading of 4 kPa, 25% strain at 0.05 Hz) on osteogenic differentiation was investigated [69] (Table 6). Short-term mechanical stimulation enhanced the expression of several genes encoding for factors involved in osteogenesis, including RUNX2, osteopontin, integrin-β1, TGFßR1, SMAD5, annexin-V and PDGFα.…”
Section: Compression Bioreactors and Combined Systemsmentioning
confidence: 99%
“…In a study by Matziolis et al, BM-derived hMSCs were cultured on human cancellous bone-fibrin composites (15 mm diameter and 4 mm thickness) in a compression bioreactor, and the effect of short term mechanical stimulation (24-hour cyclic loading of 4 kPa, 25% strain at 0.05 Hz) on osteogenic differentiation was investigated [69] (Table 6). Short-term mechanical stimulation enhanced the expression of several genes encoding for factors involved in osteogenesis, including RUNX2, osteopontin, integrin-β1, TGFßR1, SMAD5, annexin-V and PDGFα.…”
Section: Compression Bioreactors and Combined Systemsmentioning
confidence: 99%
“…For example, compression of mesenchymal stem cells seeded in cancellous bone-fibrin ‘sandwiches’ [217] increases expression of osteogenic signaling molecules [218], and a similar effect was noted for mature osteoblasts [219]. Interestingly, these responses may be further modified by imposing high frequency vibrations (~25 Hz) onto cyclic compression (3 Hz) [220].…”
Section: Models Of Applied Mechanical Loadingmentioning
confidence: 99%
“…The results demonstrated that mechanical compression upregulated several genes (see supporting information, Table S1). Six candidate genes, TGF‐β1 , Smad5 , BMP4 , BMP7 , Wnt5a and Wnt10a , were selected based on the transcriptome and several previous reports on in vivo expression implicated in odontoblastic differentiation (Feng et al ., ; Lin et al ., ; Suomalainen and Thesleff, ) and on in vitro expression by mechanical stimulation of osteoblastic differentiation (Matziolis et al ., ; Sharp et al ., ). Some genes whose expression levels were attendant on odontoblastic marker expression were identified.…”
Section: Resultsmentioning
confidence: 97%
“…Mesenchymal cells respond to various mechanical forces in vivo , including vascular endothelial cells to shear stress of blood flow (DePaola et al ., ) or hydrostatic pressure (Schwartz et al ., ), cardiomyocytes to extension force (Granzier and Irving, ) and periodontal ligament cells to occlusal and orthodontic forces (Toms and Eberhardt, ; Poiate et al ., ). In addition, several in vitro studies have shown that mechanical stimulation induces the differentiation of mesenchymal stem/progenitor cells into osteoblasts (Datta et al ., ; Sharp et al ., ; Yang et al ., ; Matziolis et al ., ), chondrocytes (Huang et al ., ; Terraciano et al ., ; McMahon et al ., ; Schätti et al ., ) and ligament cells (Altman et al ., ). Dental pulp stem cells (DPSCs) can differentiate into odontoblast‐like cells to form reparative dentine due to the pressures of condensation (amalgam), 14 lb over freshly cut dentinal tubules, high‐speed cutting and low‐speed cavity preparation as external forces (Hargreaves and Cohen, 2011).…”
Section: Introductionmentioning
confidence: 98%